An in Vitro Study Comparing Nano-Composite Microleakage with and without Hydroxyapatite-Reinforced Glass Ionomer Cement and Cention N as a Base Material in Class I Cavity - Albadah As, Khan Am (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: This study assessed microleakage in class one cavities in premolar teeth treated with Nano-composites using Cention N and Hydroxyapatite reinforced Glass ionomer cement as a base. Materials and Methods: In Sixty premolars, Class I cavities, one-fourth the intercuspal distance wide and 0.5-1mm deep were formed. Three groups were made. Group 1 received only Nano-Composites, Group 2, Nano-Composites with Cention N, and Group 3, Nano-Composites with Hydroxyapatite reinforced GIC was used as a base material. After 24 hours in distilled water, samples were undergone 5000 thermocycles at 5°C to 55°C. Samples were dried, and apical surfaces were sealed and saved for a 1mm wide zone around the restoration margins. Teeth were coloured with 2% Methylene blue. All the teeth were longitudinally sectioned and examined under a microscope Results: The least microleakage and internal gaps with GIC reinforced by Hydroxyapatite used as a base material (1.03± 0.832), followed by Nanocomposites. (2.08 ± 1.347). However, the greatest microleakage was observed with Cention N when used as a base (2.60 ± 0.928). A strong positive correlation was also observed between microleakage and internal gap formation. Conclusion: Cention N demonstrated the maximum microleakage as a base material, followed by Nanocomposite. GIC with Hydroxyapatite as a base material showed the least microleakage.